Modal Analysis for a Rod-Fastened Rotor considering Contact Effect Based on Double Fractal Model - Yang Liu; Qi Yuan; Pu Li; Guangyu Zhu (Shock and Vibration)
The rod-fastened rotor is the core component of the gas turbine. It comprises several discs and tie rods. The flexural stiffness of the contact interface is the key factor for rotordynamic analysis. The contact interfaces of the discs are usually manufactured by grinding. The measured contour curve of the contact interfaces of an experimental rod-fastened rotor is analyzed by the structural function method, which shows that the contact interfaces can be well described by the double fractal model with fractal dimensions D1 and D2 and the fractal roughness parameters G1 and G2. The Hertz model is used to analyze the contact of the single asperity on the contact interface. On this basis, the flexural stiffness of the contact interface considering the pretightening force and the bending moment is derived. Modal frequencies of the experimental rod-fastened rotor under different pretightening forces and the bending moment (caused by gravity) are obtained by three-dimensional finite element analysis and experimental modal tests. It is observed that the modal frequencies increase with the nominal pressure of the contact interface, and the experimental results are consistent with the calculated results.